Optimal scheduling of an electric–hydrogen-integrated energy system considering virtual energy storage - Zhang, Bolin; Shao, Chong; Li, Chunhua; Guo, Tingzhe; Lei, Aihu; Guan, Xinyu; Zu, Longyu (Frontiers in Energy Research, 2024)
In this paper, a two-layer optimization approach is proposed to facilitate the multi-energy complementarity and coupling and optimize the system configuration in an electric-hydrogen-integrated energy system (EH-IES). Firstly, an EH-IES with virtual energy storage is proposed to reduce the cost of physical energy storage equipment. Secondly, a two-layer optimal allocation method is proposed under a multi-timescale strategy to examine the comprehensive evaluation index of environmental protection and economy. The upper layer utilizes the NSGA-II multi-objective optimization method for system capacity allocation, while the lower layer performs economic dispatch at the lowest cost. Ultimately, the output includes the results of the equipment capacity allocation of the EH-IES that satisfies the reliability constraint interval and the daily scheduling results of the equipment. The results demonstrate that the electric-hydrogen-integrated energy system with the coupling of multiple energy equipment not only enhances the utilization of renewable energy sources but also reduces the usage of fossil energy and improves the system’s reliability.